(untitled) (ItalianoLinguadue, 2020)
Partendo dalle difficoltà di comprensione di studenti del primo anno di università, l’autrice focalizza su una zona sensibile della semantica: l’individuazione di voci diverse in un testo. Si tratta dell’aspetto enunciativo del discorso, centrale quando l’avvicendamento dei punti di vista si avvicina alla polifonia. L’ipotesi didattica è che gli strumenti narratologici, ormai un po’ consunti, possano diventare delle leve per una didattica attiva di tipo laboratoriale che ponga gli studenti davanti a problemi interpretativi cui siano motivati a dare delle risposte. One aspect of understanding: recognizing points of view. Individual competence with social value Starting from the comprehension difficulties of first-year university students, the author focuses on a sensitive area of semantics: the identification of different voices in a text. This is the enunciative aspect of discourse, which is central when the alternation of points of view approaches polyphony. The didactic hypothesis is that the narratological instruments, now a bit worn out, can become levers for active, laboratory-type didactics that put students in front of interpretative problems which they are motivated to resolve.